IMPLEMENTASI KRIPTOGRAFI DAN KOMPRESI SMS MENGGUNAKAN ALGORITMA RC6 DAN ALGORITMA HUFFMAN BERBASIS ANDROID - Laurentinus Laurentinus (Jurnal Informatika Global)
The development of telecommunications technology in the era of globalization happens very rapidly to help people to communication and one of the communication technology is using telephone device. However, the absence of security in securing data/information of delivery Short Message Service (SMS) that is confidential causes the message easily stolen by unauthorized parties. SMS sent via the BTS will be accepted Message Service Center (SMSC) been causing a crack misuse of the information. One way to secure the data from the data communication process is by cryptography. This research using descriptive statistical research methods. This research was conducted by analyzing the security by implementing the RC6 algorithm in cryptography and compression applications based on android SMS. The RC6 algorithm is an symmetric cryptographic algorithm that use the same key in encryption and decryption of SMS message. The encryption process that changes the number bits of data affects the number of SMSs that need to be sent, so text compression is required. The Huffman algorithm is a lossless data compression algorithm in which data compression does not eliminate one byte and is stored as originally. So the result of decompress is same with original ciphertext. Testing is done using Blackbox Method.This research was conducted to solve the security problem of sending SMS with cryptography and send data can be compressed to save SMS cost.Keywords : Cryptography, Encryption, Decryption, SMS, Mobile, RC6, Huffman,android